Deficyty zaufania społecznego w przestrzeniach instytucji świeckich i kościelnych. Przyczynek z badań empirycznych - Świątkiewicz, Wojciech (Studia Pastoralne, 2026)
Trust, sociologically speaking, is a foundation of social order. Not only does it function to designate moral standards with reference to social relationships taking place between individuals, groupings and institutions, but it also organizes diversified constellations of interactions which relate particular actors to social groups or institutions. When defined as an ethical category originating from the shared, community-wide acceptance of values, trust is endowed with quantifiable consequences for the quality of social life. This article comprises a brief presentation and subsequent sociological interpretation aiming to deliver the results of the sociological survey research that are exclusively focused upon trust-related considerations observed with reference to selected institutions, as well as chosen representatives of ecclesiastical and secular spheres of social life. By way of conclusion, the paper postulates that social trust constitutes a moral dilemma which refers not only to the functioning of public authorities and the applied standards of governance. Likewise, it is also indicative of the Roman Catholic Church. Furthermore, it is argued that the significance of trust cannot be downplayed either by political or ecclesiastical authorities. Nevertheless, one is in a position to observe a significant difference between the two great social structures encompassing the Polish society. This discrepancy is discernible especially when the deficits of social trust are being measured. Poles, in the main, are willing to vest trust in the Church. Yet, at the same time, the respondents remain distanced with regard to public authorities, institutions, organizations, and individuals who fulfill the social role of leaders.